Promoting learning skills through teamwork assessment and self/peer evaluation in higher education - Issa, Tomayess (IADIS Press, 2012)
In the education sector, teamwork assessment and self/peer evaluation are widely applied in higher education nationally and internationally. This assessment is designed to encourage students to promote and improve their skills in teamwork, communication (writing, interpersonal interaction and cultural awareness, and presenting), critical and creative thinking (problem solving and decision-making), Information Technology literacy, and information literacy. Beside the above, this assessment will improve work performance and productivity and increase self-confidence in a range of situations. These skills are developed by formative and summative feedback, collaboration, and cooperation between students and the lecturer. This study aims to discuss the development of teamwork assessment and self/peer evaluation in the BT2 undergraduate unit at an Australian university to promote students’ skills and to prepare them for the workplace in the future, as most of these skills are indispensable not only from the academic perspective but for business as well. This study provides empirical evidence from 267 students, based on quantitative and qualitative data derived from two sources. The first is the anonymous informal feedback collected during the semester, while the second (formal) source of students’ evaluations and perspectives towards the BT2 unit is ‘eVALUate’, the anonymous online system for gathering and reporting students’ perceptions of their learning experiences at the university. The students’ remarks show their satisfaction with this assessment, as it develops specific skills for the current study and for the future workplace, i.e. time management; problem solving, decision-making, cultural awareness, presentation, communication and meeting a deadline.